2020
DOI: 10.1186/s12905-020-01006-5
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative assessment of knowledge and attitudes towards cervical cancer screening among male Latino immigrants in Houston, Texas

Abstract: Background: Male spouses and partners play an important role in determining a woman's willingness to participate in cervical cancer screening. However, the attitudes and behaviors by which they influence a woman's decision to undergo Pap testing remain poorly understood. Methods: A series of semi-structured, qualitative interviews were conducted in Spanish with 19 recent Latino immigrants in Houston, Texas. The interview format was designed to establish each individual's pattern of engagement with the United S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
2
0
0
Order By: Relevance
“…Findings are consistent with previous studies conducted in Kenya [ 9 ], Ghana [ 8 ], South Africa [ 10 ] and among Latino immigrant [ 24 ] and Sub-Saharan African immigrant men in the United States [ 25 ] that similarly found that men had inadequate or inaccurate knowledge on cervical cancer. However, men have expressed willingness to learn more to enhance support of their partners’ health seeking behaviours for screening [ 6 , 8 , 26 ] as was also inferred in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Findings are consistent with previous studies conducted in Kenya [ 9 ], Ghana [ 8 ], South Africa [ 10 ] and among Latino immigrant [ 24 ] and Sub-Saharan African immigrant men in the United States [ 25 ] that similarly found that men had inadequate or inaccurate knowledge on cervical cancer. However, men have expressed willingness to learn more to enhance support of their partners’ health seeking behaviours for screening [ 6 , 8 , 26 ] as was also inferred in this study.…”
Section: Discussionsupporting
confidence: 91%
“…This study gives insight into the fact that husbands' support is such an important factor affecting reproductive health service utilization, including cervical cancer screening, which is also consistent with other studies (10,29). This is particularly prevalent in Africa, where most women's reproductive issues and utilization of reproductive services, including CCS, are under the approval of their husbands (11,25,26).Thus, interventions are needed to enhance knowledge of cervical cancer and screening and improve trust in the health care system among male spouses or partners, which is consistent with studies (7,18,28). Taking interventions to correct misconceptions about cervical cancer and screening is also a key strategy to achieving the global strategy, which sets 90-70-90 targets for elimination that must be met by 2030.…”
Section: Discussionsupporting
confidence: 83%